Nursing Profession, Caring and Discipline - Wiwin MARTININGSIH; Sri Winarni; Angelito Estoesta Alvarado (Humanistic Network for Science and Technology (HNST), 2021)
Nursing indeed is the art of caring and selfless giving of time, effort, love, and care. The patient is the center of nursing, and it is their responsibility to make sure they are receiving the right care that they can receive. There are so many ways to show caring that the possibilities never end. The purpose of this study was to generate knowledge which informed caring in nursing as a discipline within applying attributes of caring. Mayeroff and Roach’s attributes guided the concept analysis within the theoretical perspective of caring. The emerging themes are: Caring as the central focus of Nursing, Caring as a Profession and Discipline, Our perspective of caring, Our idea of a caring nurse, and How does Nurse care for others. Caring is everything and nurse should applying attributes of caring in the fields of nursing. Caring is not only able to care for the client, but also how the client is satisfied and the nurse always continues to improve knowledge and be innovative and creative. Keywords: nursing profession; caring; discipline